ENHANCING STUDENTS’ SPEAKING ABILITY THROUGH INTERVIEW TECHNIQUE - Naufal Azmi; Ismalianing Eviyuliwati; Maya Defianty (XXXXXXXX, 2024)
The study aims at enhancing students’ speaking ability through interview technique. This study is conducted on 26 students of the eighth-grade of SMPN 9 Tangerang Selatan in Academic Year 2018/2019. This study uses Classroom Action Research as the research method which was designed by Kurt Lewin. The study is conducted in two cycles where each cycle consists of planning, acting, observing, and reflecting. The data are obtained through tests (pre-test, post-test 1, post-test 2). The result of the study shows that there is an enhancement in students’ speaking ability. The students’ enhancement is proved by their speaking test result which improves from test to test. In the pre-test, there are only 11.53% or 3 students who could pass the Minimum Mastery Criterion (KKM), and the mean score is 51.53. Then, in the post-test 1 in Cycle 1, there are 19.23% or 5 students who pass the KKM, and the mean score is 60.  Therefore, there is a little enhancement from the pre-test to post-test 1. Finally, in post-test 2, it shows that the enhancement is quite large that there are 80.76% or 21 students who can pass the KKM, and the mean score is 77.07. Thus, this indicates that it has met the criterion of success that at least 75% of students must get the score above the KKM